Actinidia chinensis Planch Ameliorates Photoaging in UVB-Irradiated NIH-3T3 Cells and SKH-1 Hairless Mice by Controlling the Reactive Oxygen Species/AKT Pathway - Jong-Min Jung; Seo-Young Kim; Oh-Yun Kwon; Seung-Ho Lee (MDPI AG, 2024)
In this study, we evaluated the antiphotoaging properties of Actinidia chinensis Planch (ACP) and the molecular mechanisms underlying its ability to prevent UVB-mediated photoaging. Administration of the ethanolic extract of ACP (EEACP) to the dorsal area of hairless mice effectively ameliorated UVB-mediated wrinkle formation, epidermal thickening, and loss of lipid droplets in the epidermis. Additionally, the UVB-induced loss of collagen content in the epidermis was significantly attenuated in mouse skin treated with EEACP. The expression of procollagen type 1 and metalloproteinase-1a, which are related to collagen content in the epidermis, was restored by EEACP treatment in UVB-irradiated mice and NIH-3T3 mouse skin fibroblast cells. Interestingly, EEACP effectively ameliorated UVB-induced reactive oxygen species overproduction. Furthermore, the activation/phosphorylation of AKT, rather than mitogen-activated protein kinases, has been identified as a major target of EEACP in preventing UVB-mediated photoaging. Additionally, N-(1 deoxy-1-fructosyl) valine and phenethylamine glucuronide were identified as analytical indicators of EEACP using high-performance liquid chromatography/mass spectrometry. These results suggest that EEACP can be developed as a functional natural agent capable of preventing photoaging by attenuating UVB-induced activation of the reactive oxygen species/AKT pathway.